The complete mitochondrial genome of Urocitellus undulatus and its phylogenetic analysis - Zimeng Liu; Lei Chen; Yuran Pang; Xing Yang; Fengyan Zhang; Tangxin Liu; Xinhui Zhang; Yayun He; Xu He; Jiaxin Wang; Qingsong Sun (Mitochondrial DNA. Part B. Resources)
The long-tailed ground squirrel (Urocitellus undulatus) is primarily distributed in various regions, including Xinjiang and Heilongjiang in China, as well as in Siberia, Mongolia, the Russian Federation, and Kazakhstan. In this study, we report the complete mitochondrial genomes of U. undulatus. The genome consists of 16,456 base pairs, including 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region. The phylogenetic relationship indicates a closer evolutionary relationship between U. undulatus and U. richardsonii. These findings provide a foundation for the taxonomic identification, phylogenetic evolution, and mitochondrial genome research of U. undulatus.